Additions to Neoperla caii Li & Wang and description of Kamimuria petasus sp. nov. from China (Plecoptera: Perlidae) - Chen, Zhi-Teng (Zootaxa, 2019)
Additional specimens of Neoperla caii Li & Wang, 2017 are recorded from Sichuan Province of southwestern China. Morphological variation in the adult male is discussed and illustrated. The adult female of N. caii is described and illustrated for the first time. In addition, a new species, Kamimuria petasus sp. nov. is described from Sichuan Province. The adult male of this new species is characterized by subtriangular basal callus on the hemitergal lobe and by the aedeagus with a hat-shaped apex.